Targeting immunometabolism during cardiorenal injury: roles of conventional and alternative macrophage metabolic fuels - Mouton, Alan J.; do Carmo, Jussara M.; da Silva, Alexandre A.; Omoto, Ana C. M.; Hall, John E. (Frontiers in Physiology, 2023)
Macrophages play critical roles in mediating and resolving tissue injury as well as tissue remodeling during cardiorenal disease. Altered immunometabolism, particularly macrophage metabolism, is a critical underlying mechanism of immune dysfunction and inflammation, particularly in individuals with underlying metabolic abnormalities. In this review, we discuss the critical roles of macrophages in cardiac and renal injury and disease. We also highlight the roles of macrophage metabolism and discuss metabolic abnormalities, such as obesity and diabetes, which may impair normal macrophage metabolism and thus predispose individuals to cardiorenal inflammation and injury. As the roles of macrophage glucose and fatty acid metabolism have been extensively discussed elsewhere, we focus on the roles of alternative fuels, such as lactate and ketones, which play underappreciated roles during cardiac and renal injury and heavily influence macrophage phenotypes.